Perlindungan Hukum bagi Pelamar CPNS Terkait Batas Usia dalam Hukum Kepegawaian - Harmaini, Harmaini; Arqon, Mohammad; Salman, Salman; Siregar, Ade Uli Kurniati; Amirullah, M Aria (PT. Meja Ilmiah Publikasi, 2025)
This research aims to analyze the legal protection for applicants of the Civil Servant Candidates (CPNS) regarding the age limit policy in Indonesia, examining the dualism between its legal basis and the potential for discrimination from a Human Rights (HAM) perspective. This study employs a normative juridical research method with a statutory and conceptual approach. Data were qualitatively analyzed from primary legal materials, such as Law No. 5 of 2014 and Government Regulation No. 11 of 2017, as well as secondary legal materials. The findings indicate that while the age limit policy is strongly grounded in law and administrative rationality for efficiency and productivity, it inherently risks creating age-based discrimination. This rigid policy conflicts with the non-discrimination principle in human rights as it may exclude competent candidates based on age stereotypes. The impact of this research is a recommendation for the government to re-evaluate the existing policy towards a more flexible, substantive, and competency-focused recruitment system to ensure justice and equal opportunities for all citizens.